Changes in Blood Factors and Ultrasound Findings in Mild Cognitive Impairment and Dementia - Cho, Kyoungjoo; Kim, Jihye; Kim, Gyung W. (Frontiers in Aging Neuroscience, 2017)
The present study aimed to assess the changes in blood factors and ultrasound measures of atherosclerosis burden patient with MCI and dementia. Peripheral blood samples and ultrasonography findings were obtained for 53 enrolled participants. Flow cytometry was used to evaluate levels of activated platelets and platelet-leukocyte aggregates (PLAs). The number of platelets expressing p-selectin was correlated with IMT (intima media thickness) and plaque number in both the MCI and dementia groups. The number of platelets expressing p-selectin glycoprotein ligand (PSGL) was strongly correlated with IMT in patients with MCI, whereas the number of platelets expressing PGSL was correlated with plaque number rather than IMT in patients with dementia. PLAs was associated with both IMT and plaque number in patients with MCI but not in those with dementia. Our findings demonstrate that alterations in IMT and plaque number are associated with an increased risk of cognitive decline as well as conversion from MCI to dementia and that blood factor analysis may aid to detect the severity of cognitive decline.